PROFILE OF PATIENTS WITH CHRONIC HEPATITIS C IN A PUBLIC HEALTH PROGRAM IN SOUTHERN BRAZIL - MINME,Roseline (2018)
ABSTRACT BACKGROUND: Chronic hepatitis C (CHC) can progress to cirrhosis and its complications as hepatocellular carcinoma, leading to morbidity and mortality. To know the profile of patients with CHC virus is fundamental to optimize management. OBJECTIVE: To describe the profile of patients with CHC in a public health program in Southern Brazil. METHODS: A retrospective study was carried out in patients with CHC who underwent treatment against hepatitis C virus in a dispensation and pharmaceutical assistance center of the Public Health Department of the State of Rio Grande do Sul, South Brazil. All medical records of patients attended between December/2015 and December/2016 were evaluated. RESULTS: A total of 1,431 records of patients with CHC were evaluated. Males were the most prevalent (802; 56%) patients. The mean age was 58.6±9.9 years, ranging from 18 to 89 years. Genotype 1 was the most frequent (866;60.5%) of the patients. Ninety (6.3%) patients were transplanted from a solid organ, and of these, 73 (5.1%) were transplanted from the liver. The fibrosis evaluation was performed in 1,300 (90.8%) patients. Of these, 566 (39.6%) were evaluated through liver biopsy. Regarding the degree of fibrosis, 779 (54.4%) presented fibrosis grade 4 (cirrhosis). The genotype 3 was the most associated with fibrosis grade 4, and genotype 1 was associated with high viral load. CONCLUSION: The present study made possible the evaluation of the characteristics of patients with CHC in a public health program in South Brazil. There was a predominance of CHC in males, and the mean age was 59 years. They presented a predominance of genotype 1, higher viral load in patients with genotype 1 and greater degree of fibrosis in patients with genotype 3.